Struggling for Religion in Jewish Scientific Research—Max Wiener’s Critique on Hermann Cohen’s Notion of Religion - Stünkel, Knut Martin (European journal of jewish studies, 2021)
Abstract The article examines Max Wiener’s thoughts on the relation of Judaism and religion via his critique of his former teacher, Hermann Cohen. This focusses on the notion of religion developed by Cohen in the context of Jewish Scientific Research [ Wissenschaft des Judentums ]. It discusses Wiener’s thoughts on religion in order to exemplify the specific kind of struggle a non-Christian religious tradition might get into concerning the application of the notion of religion upon itself.